Synchronous bilateral torsion of nonpathological ovaries in an adolescent girl with unilateral recurrence - Richa Vatsa; Vidushi Kulshrestha; Juhi Bharti; Seema Singhal; Neena Malhotra (Gynecology and Minimally Invasive Therapy, 2023)
Synchronous bilateral ovarian torsion is rare that too in nonpathological ovaries. To the best of our knowledge, this is the second case of synchronous bilateral ovarian torsion of nonpathological ovaries in adolescents. A 14-year-old girl presented with pain lower abdomen, vomiting, and constipation for the last 10 days. Ultrasonography (USG) suggested bilateral ovarian torsion without any ovarian pathology. Emergency laparoscopy confirmed bilateral ovarian torsion with necrosed-looking ovaries, and detorsion was done. During follow-up period, she had intermittent mild pain abdomen, and on USG, her left ovary returned to normal size, but her right ovary had been bulky throughout without any cyst. At around 10 months, the patient presented with severe abdomen pain. This time only right ovarian torsion was there. Laparoscopic bilateral ovarian detorsion with bilateral ovarian ligament plication was done. Ovarian torsion can be bilateral, even in nonpathological ovaries. Ovarian fixation should be done in these cases to prevent recurrent torsion.